Salwa Cars Structure Testing Standards Regulation Formula Society of Automotive Engineers - Dwi Jatmoko; Agus Haryadi; Arif Susanto; Aci Primartadi; Mohammad Reza Listiana (Jurnal E-Komtek, 2022)
This research was to find out the results of the bending and torsional stiffness testing of the SALWA car according to Formula SAE 2021 regulations. The research method was by designing through Solidworks 2014 software. Testing of test specimens referred to Formula SAE 2021 regulations. The front impact test results produced max Von Mises 1046.921 MPA with a displacement of 8,540 mm; the rear impact test resulted in a max Von Mises of 222,529 MPa with a max displacement of 6.85 mm; and the side impact test resulted in max Von Mises Stress of 104.15 MPa with a max displacement of 9,116 mm. In the front torsional test, the max Von Misses Stress reached 135,266 MPa with a total max displacement of 4,844 mm. The rear torsional test had a max Von Mises Stress value of 147,144 MPa with a displacement of 5.51 mm. The feasibility test still found connection and construction placement errors, and there was a low Factor of Safety value. In conclusion, the construction of the SALWA Electric Car prototype frame is not in accordance with Formula SAE regulations.